Synthesis, Characterization, and Magnetic Properties of Iron(II) Complex with 2,6-Bis(pyrazol-3-yl)pyridine Ligand and Tetracyanonickelate Anion - Fitriani Fitriani; Irma Mulyani; Djulia Onggo; Kristian Handoyo Sugiyarto; Ashis Bhattacharjee; Hiroki Akutsu; Anas Santria (Indonesian Journal of Chemistry, 2023)
The complex containing iron(II), 2,6-bis(pyrazol-3-yl)pyridine (3-bpp) as ligand, and tetracyanonickelate as counter anion has been synthesized and characterized. The characterization data suggest the corresponding formula of [Fe(3-bpp)2][Ni(CN)4]·4H2O. Meanwhile, the SEM–EDX analysis image confirms the existence of all elements contained in the complex except the hydrogen atom. The infrared spectra exhibit vibration bands of the functional groups of 3-bpp ligand and [Ni(CN)4]−1 anion. From magnetic property measurement, the complex's molar magnetic susceptibility (XMT) value is 2.65 emu mol−1 K at 300 K, which contains about 75% high-spin state of the Fe(II) complex. Upon lowering the temperature, the XMT value gradually decreases around 1.37 emu mol−1 K at 13 K. It decreases sharply to about 0.73 emu mol−1 K at 2 K. These values reveal that Fe(II) complex is in the low-spin (LS) state. As a result, the complex exhibited spin-crossover characteristics of gradual transition without thermal hysteresis, and the transition temperature occurred below room temperature with a transition temperature (T1/2) close to 140 K. The spin crossover property of the complex is supported by a thermochromic reversible color change from red-brown at room temperature to dark brown on cooling in liquid nitrogen associated with the high-spin to low-spin transition.